The Wiley handbook on what works with girls and women in conflict with the law: a critical review of theory, practice, and policy - Brown, Shelley L.; Gelsthorpe, Loraine (Wiley Blackwell, 2022)
"What Works with Girls and Women in Conflict with the Law is a book about imperatives, ideas, and initiatives. Imperatives include the need to recognise women and girls as distinct groups of people mired in criminal justice systems. Ideas and initiatives refer to the extant What Works evidence-base germane to girls and women in conflict with the law. Or more accurately, in the words of Gill McIvor (Chapter 15) due to the nascent nature of the evidence-base, the book details What Might Work to divert girls and women from crime, and what might minimize contact with criminal justice systems that at times, damages rehabilitation efforts. The What Works paradigm strives to achieve two over-arching goals. First, to accumulate research that explores the causes, and ultimately the prevention and re-occurrence of criminal conduct. Second, to translate the aforementioned cumulative knowledge base into practice. Those of us who work within the What Works movement germane to girls and women in conflict with the law share similar values with our What Works counterparts; the overall aim of both perspectives is to prevent and reduce the rate at which women and girls come in contact with the justice system by implementing the best available evidence. But we have additional goals. We may also be human rights' advocates; we may draw attention to, and ultimately try to eliminate, the unimaginable reality that many incarcerated women around the world remain shackled during labour and childbirth (see Chapter 27). Similarly, we may also be social change agents who lobby for the abolition of prison systems entirely, or actively challenge laws that impede formally incarcerated women from gaining access to affordable and safe housing, employment opportunities, or reunification efforts with their children. We may investigate the benefits of holistic programs that simultaneously targets trauma, addictions and mental health whilst recognizing that these "individual" or "personal" needs are unequivocally enmeshed within a broader political and social fabric characterized by injustices. Also, we are statistically more likely to address these aforementioned goals as mixed methodologists, embracing both qualitative and quantitative approaches rather than solely relying on quantitative methods"--